2019
DOI: 10.22207/jpam.13.4.57
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Colony Morphology, Sporophore Characters and Yield Performance of Wild and Cultivated Milky Mushroom Isolates

Abstract: The present investigation was carried out to identify morphology and yield performance of milky mushroom isolates for both the wild and cultivars. In this study, 17 wild isolates (CBE-TNAU-1513 to 1526, CBE-TNAU-1603, 1604 and CBE-TNAU-1701), seven cultivated strains (CI-13-02, 04, 06 and CI-14-02, 03, 04 and CI-14-06) and Tamil Nadu Agricultural University APK2 (C. indica) variety were compared. Colony characters of all the 25 isolates of milky mushroom grown on PDA medium were recorded. Among the isolates, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In a similar study, cultivation trial analysis of the twenty-five strains of C. indica established CBE-TNAU-1523 strain as a high yielding strain (194.5% BE) followed by APK-2 (184.5% BE) [14]. Similarly, Kavitha et al [38] reported maximum yield in Bheema (157% BE) as compared with IIHR Ca-1 (104% BE) and APK-2 (101% BE).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In a similar study, cultivation trial analysis of the twenty-five strains of C. indica established CBE-TNAU-1523 strain as a high yielding strain (194.5% BE) followed by APK-2 (184.5% BE) [14]. Similarly, Kavitha et al [38] reported maximum yield in Bheema (157% BE) as compared with IIHR Ca-1 (104% BE) and APK-2 (101% BE).…”
Section: Resultsmentioning
confidence: 79%
“…campanulate cap shape with incurved margin (DMRO-321, DMRO-202 and DMRO-316); brown pigmented cap/scurfy scales in stipe (DMRO-320, and DMRO-325) and convex to irregular cap shape (DMRO-528) (Supplementary Figure S1). Similarly, Bhupathi and Subbaiah [14] reported variations in color and fruit body (pileus-stipe) shape in different strains of C. indica. and identified eight high yielding strains in C. indica as compared with the commercially released strain (DMRO-302).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation